2013
DOI: 10.1007/s00256-013-1713-5
|View full text |Cite
|
Sign up to set email alerts
|

Access routes and reported decision criteria for lumbar epidural drug injections: a systematic literature review

Abstract: The most commonly used access routes for epidural drug injection are the interlaminar and transforaminal pathways at the level of the pathology. Transforaminal routes are being performed with increasing frequency in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…11 Extensive spinal fusion and/or scoliosis make translaminar LP a high-risk and complicated route of access to thecal space and there have been reports of patients who refused to have additional injections due to the difficulty of the procedure. 13,14 In these patients, transforaminal LP is an alternative route for the administration of nusinersen intrathecally.…”
Section: Discussionmentioning
confidence: 99%
“…11 Extensive spinal fusion and/or scoliosis make translaminar LP a high-risk and complicated route of access to thecal space and there have been reports of patients who refused to have additional injections due to the difficulty of the procedure. 13,14 In these patients, transforaminal LP is an alternative route for the administration of nusinersen intrathecally.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians believe that TF-ESI exhibits superior efficacy and is being performed with increasing frequency, although this belief seems to be unsubstantiated. 23 , 38 , 39 , 55 Our study has demonstrated that TF-ESI and C-ESI are similarly effective in managing lumbosacral radicular pain. Before selecting a steroid injection route for the management of radicular pain, the benefits and risks of the approaches discussed herein must be taken into consideration, as the outcomes of this review were not significantly different between the 2 treatment groups.…”
Section: Discussionmentioning
confidence: 74%
“…Our interventional approach also fits into the current trend toward increased use of transforaminal access routes in periradicular infiltration therapy or ESI [24]. Therefore, the protocol presented here should be of interest to most interventional radiologists.…”
Section: Discussionmentioning
confidence: 90%